Technical and cost analysis of an electric hand plow tractor for specific land in Java, Indonesia - Nandar, Cuk Supriyadi Ali; Utomo, Setyo Margo; Purnomo, Endra Dwi; Aziz, Amiruddin; Amelia, Lia; Mubarak, Achmad Ridho; Marsalyna, Marsalyna; Saraswati, Sherly Octavia; Nugroho, Fandy Septian (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This study focuses on the technical and cost analysis of an electric hand plow tractor, especially in the East Java region. The manufacturing cost of electric tractors increases significantly in line with the battery capacity. Although the manufacturing cost of an electric tractor is 3–5 times higher than that of a fuel tractor, the operational cost of an electric tractor is about 79% that of a fuel tractor. Based on the investment analysis, it is feasible to assembly electric tractors with a power of 5.5 HP or 4.1 kW using NMC18650 and NMC21700 batteries with an energy capacity of 14 kWh in case for rural residents with access to an electricity network available in their paddy fields. The price of electricity and the unit cost of a battery pack have a large impact on operational costs. The manufacture of electric tractors will be more attractive to get better economic returns when the price of electricity does not increase, and the unit cost of battery packs falls due to the battery technology trend. Nevertheless, certain challenges to the utilization of electric tractors are the farmers' preferences and habits, market demands, the environment, and the regulations of the tractor component manufacturers.